Application of artificial neural networks for prediction of natural convection from a heated horizontal cylinder - Ataylimaz, S. Oezguer; Demir, Hakan; Agra, Oezden (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
A generalized neural network analysis for natural convection heat transfer from a horizontal cylinder is developed in this paper. Cylinder diameter, cylinder surface temperature and ambient temperature are selected as the input parameters. while the Nusselt number as the output A three-layer network is used for predicting the Nusselt number The number of the neurons in the hidden layer was determined by a trial and error process together with cross-validation of the experimental data evaluating the performance of the network and standard sensitivity analysis analysis The trained network gives the best values over the correlations with less than 2.5% mean relative error The experimental data of the average Nusselt number over the horizontal cylinders having different diameters of 4.8 mm-9.45 mm are from Atayilmaz and Teke [1] The results from the trained network were compared with the proposed correlation for the average Nusselt number over the cylinder and it is shown that the results are in satisfactory agreement. The Nusselt numbers obtained from the experimental study were seen to be consistent by +/-20% with the well known correlations for natural convection heat transfer front horizontal cylinder developed by Morgan [2], Fand and Brucker [3], and Churchill and Chu [4] Moreover it is seen that that results from the trained network show absolute agreement with the experimental data in +/- 5% in deviation band better than the correlations given by Morgan [2], Fand and Brucker [3]. and Churchill and Chu [4]. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Neural network; Natural convection; Heat transfer; Horizontal cylinder; EQUATIONS; LAMINAR; Thermodynamics; Mechanics